2021
DOI: 10.1017/wet.2021.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cover-crop biomass, strip-tillage residue disturbance width, and PRE herbicide placement on cotton weed control, yield, and economics

Abstract: Conservation tillage adoption continues to be threatened by glyphosate and acetolactate synthase-resistant Palmer amaranth and other troublesome weeds. Field experiments were conducted from autumn 2010 through crop harvest in 2013 at two locations in Alabama to evaluate the effect of integrated management practices on weed control and seed cotton yield in glyphosate-resistant cotton. The effects of a cereal rye cover crop using high or low biomass residue, followed by wide or narrow within-row strip-tillage, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Consequently, the cereal rye biomass and groundcover were greatly reduced when compared to 2020, where the cereal rye in 2019 measured less than 40 cm in height and the cereal rye in 2020 was approximately 150 cm tall. Cereal rye biomass at planting was not measured in 2019, but biomass of the cereal rye at planting in 2020 averaged 4,500 kg ha −1 , which is similar to biomass recovered in other studies where weed emergence was suppressed at biomass levels ≥ 3,100 kg ha −1 (Palhano et al 2018;Price et al 2021). Differences in herbicide programs between 2019 and 2020 can be attributed to differences in climatic conditions between the two years (Figure 2).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Consequently, the cereal rye biomass and groundcover were greatly reduced when compared to 2020, where the cereal rye in 2019 measured less than 40 cm in height and the cereal rye in 2020 was approximately 150 cm tall. Cereal rye biomass at planting was not measured in 2019, but biomass of the cereal rye at planting in 2020 averaged 4,500 kg ha −1 , which is similar to biomass recovered in other studies where weed emergence was suppressed at biomass levels ≥ 3,100 kg ha −1 (Palhano et al 2018;Price et al 2021). Differences in herbicide programs between 2019 and 2020 can be attributed to differences in climatic conditions between the two years (Figure 2).…”
Section: Resultssupporting
confidence: 73%
“…In 2020, the use of cereal rye improved cotton yields by 220 kg ha −1 and profit by US$280 ha −1 . The improvement in cotton yield because of cereal rye is similar to findings in Alabama and Tennessee, where the use of a cover crop did improve cotton yields in some years, while there were negligible differences in others (Price et al 2021;Zhou et al 2017). Findings from other studies in Arkansas and Texas suggested that the use of cereal rye cover crops had no effect on cotton yield or net returns (DeLaune et al 2020;DeVore et al 2012).…”
Section: Impact On Cotton Production Economicssupporting
confidence: 77%
See 2 more Smart Citations
“…Included in integrated strategies is an increased use of tillage to bury weed seeds at depths beyond successful germination and emergence, which threatens adoption and retention of conservation systems (Price et al 2011(Price et al , 2016. However, the adoption of cover crops continues to gain attention because of their weed-suppressive attributes, including disrupting the establishment and growth of weeds while maintaining crop yields (Aulakh et al 2015;Norsworthy et al 2010Norsworthy et al , 2011Price et al 2011Price et al , 2016Price et al , 2021. Weed suppression after cover crop termination has been shown primarily to be due to plant residue biomass that prevents seed germination and establishment by altering light quantity at the soil surface and providing a physical barrier (Norsworthy et al 2011;Price et al 2006;Teasdale 2018).…”
Section: Introductionmentioning
confidence: 99%